Validation of the DnaK-DnaJ-GrpE chaperone complex as a drug target in Mycobacterium tuberculosis - Kapambwe, Mirriam Chishala (Rhodes University, 2026)
Embargo applied. Embargo period to expire in October of 2027.
Keywords: Uncatalogued